Application of zirconium caged activated biochar alginate beads towards deionization of Cr(VI) laden water in a fixed bed column reactor. Issue 4 (August 2018) - Banerjee, Soumya; Joshi, S.R.; Mandal, Tamal; Halder, Gopinath
Highlights: Fixed bed column was packed with Zr caged activated biochar alginate beads. This column was tested for Cr(VI) removal both from single and multi-ion solution. Maximum removal was found at bed height of 30 cm and 1 mL/min of flow rate. The column survived for 7 desorption-adsorption cycles regenerated via NaOH. Dynamic models were used in formalizing the process for its use at larger scale. Abstract: An investigation of dynamic fixed bed loaded with zirconium caged steam activated biochar alginate bead was performed towards deionization of Cr(VI) laden aqueous solution. Impact of process parametric factors which include bed height (5 to 30 cm), initial influent concentration (10 to 60 mg/L) and flow rate (1 to 4 mL/min) were studied at a constant pH of 3 ± 0.5 from a synthetic non-competitive Cr(VI) solution. As interpreted from the experimentations it was observed that with every increase in bed height, length of the breakthrough curve also increased. On the contrary to bed height, increase in metal concentration and flow rate with predefined bed height efficacy of the column decreased. The adsorbent bed was able to retain 499.5 mg of ions with an uptake of 116.805 mg/g from an optimum influent metal concentration of 50 mg/L at a flow rate of 1 mL/min. A removal of 93.54% was observed at this optimum condition. The process was evaluated with bed depth service time model, Thomas and Yoon-Nelson model which substantiated the findings. From desorption-adsorption cycle it was observed that the column retained its removal efficacy up to 7 cycles with a column regeneration percentage of 51.108%. This adsorbent was capable of removing Cr(VI) from a multi-ion synthetic waste water solution where the breakthrough curve showed similarity with 10 mg/L of synthetic single Cr(VI) ion solution. Thus, the prepared zirconium caged adsorbent could be used in a fixed bed column reactor towards remediating metal ions from contaminated aqueous solution.